Spatial and temporal variations of the 3-year earthquake swarm activities leading up to the M7.6 Noto Peninsula earthquake and interpretations of their activities - Takao Kumazawa; Yosihiko Ogata (Earth, Planets and Space)
Abstract The seismic swarm activity that began and expanded in four separate regions in the northern Noto Peninsula at the end of 2020 was followed by the M6.5 earthquake in May 2023, which cascaded into the M7.6 earthquake on New Year’s Day 2024. To this series of earthquake events, we estimate temporal changes in the background intensity of the nonstationary ETAS model by inversion for each region. We then interpret how this series of earthquakes was driven by subsurface fluid motion and slow slip at each stage, based on the correspondence between the background seismicity changes and the temporal changes in oblique distance and elevation differences between nearby GNSS stations, as well as the spatiotemporal earthquake patterns. Graphical Abstract